[(18‐Crown‐6)K][Fe(1)Cl(1)4]0.5[Fe(2)Cl(2)4]0.5: A Multifunctional Molecular Switch of Dielectric, Conductivity and Magnetic Properties. Issue 6 (19th February 2018) - Tong, Yuan‐Bo; Tian, Zheng‐Fang; Duan, Hai‐Bao; Zhu, Zhong‐Peng; He, Wei; Hong, Tian‐Yu; Yu, Gui; He, Yu‐Jian; Yang, Jing‐Kui
Abstract: Multifunctional materials that exhibit different physical properties in a single phase have potential for use in multifunctional devices. Herein, we reported an organic–inorganic hybrid compound [(18‐crown‐6)K][Fe(1)Cl(1)4 ]0.5 [Fe(2)Cl(2)4 ]0.5 (1 ) by incorporating KCl and FeCl3 into a 18‐crown‐6 molecule, which acts as a host of the six O atoms providing a lone pair of electrons to anchor the guest potassium cation, and [FeCl4 ] − as a counterion for charge balance to construct a complex salt. This salt exhibited a one‐step reversible structural transformation giving two separate high and low temperature phases at 373 K, which was confirmed by systematic characterizations including differential scanning calorimetry (DSC) measurements, variable‐temperature structural analyses, and dielectric, impedance, variable‐temperature magnetic susceptibility measurements. Interestingly, the structural transformation was coupled to both hysteretic dielectric phase transition, conductivity switch and magnetic‐phase transition at 373 K. This result gives an idea for designing a new type of phase‐transition materials harboring technologically important magnetic, conductivity and dielectric properties. Abstract : Multifunctional crown : A hybrid supramolecular complex of [(18‐crown‐6)K][Fe(1)Cl(1)4 ]0.5 [Fe(2)Cl(2)4 ]0.5 shows reversible hysteretic magnetic phase transitions and a dielectric anomaly as well as a conductivity switch. The switch natures are related to the structure phase transition triggered by temperature changing.